Photocatalytic Degradation of Methylene Blue on Fe-Fullerene/TiO2 Under Visible-Light Irradiation - Meng, Za-Da; Cho, Kwang-Youn; Oh, Won-Chun (Asian Journal of Chemistry, 2010)
Three types of Fe-fullerene/TiO2 were prepared using C60 (fullerene) and titanium(IV) nbutoxide by a modified sol-gel method. The prepared photocatalysts were characterized by X-ray diffraction, transmission and scanning electron microscopy, energy dispersive X-ray analysis and photocatalytic activity. Photocatalytic properties for decolorization of methylene blue solution in the presence of three types of Fe-fullerene/TiO2 under visible light had been studied. The results showed that Fe incorporated fullerene enhanced TiO2 increase the decolorization rate of methylene blue. It was found that the photocatalytic degradation of a methylene blue solution could be attributed to the combined effects caused by the photo-degradation of titania, the electron assistance of fullerene, the enhancement of Fe by photo-fenton effect. The presence of Fe enhanced the photocatalytic actiity of Fe-fullerene/TiO2 catalysts under visible light.